Route Planning with Breaks and Truck Driving Bans Using Time-Dependent Contraction Hierarchies - van der Tuin, Marieke; de Weerdt, Mathijs; Batz, G. (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
Mandatory breaks for truck drivers are nowadays scheduled after the route has been decided. However, in some cases it is beneficial to plan these breaks during waiting time caused by truck driving bans. Optimally planning a single break considering driving bans can be done using Dijkstra’s algorithm with multiple labels. This has large effects on predicted travel times: 17% of the analysed routes having a night rest obtain an earlier arrival time by 5 hours on average. However, the computation times of this algorithm are long. A novel heuristic version of time-dependent contraction hierarchies leads to significant reductions in computation times from several seconds to several milliseconds per route. Experiments show that the solutions are still optimal for a representative test set consisting of 10,000 route queries.